The role of explicit solvent molecules in the calculation of NMR chemical shifts of glycine in water - Caputo, Maria Cristina (2018)
We present the results of a computational study of the NMR properties of glycine in water solution at the level of density functional theory employing the B3LYP functional and the 6-31G(d,p) and pcSseg-2 basis sets, describing the solvent either via the PCM continuous solvation model or PCM with additional explicit water molecules hydrogen-bonded to the solute. We observe that the solvent causes considerable changes in the predicted magnetic shieldings and that the results depend significantly on the number of solvent molecules included in the quantum mechanical treatment.